Perceived Effectiveness of Educational Module on Brucellosis in Dairy Animals - Verma, Arjun Prasad; Meena, Hans Ram; Patel, Diksha (Indian Journal of Extension Education, 2021)
The study was carried out in six district of Haryana and Punjab state to assess the perceptions of dairy farmers on effectiveness of educational modules on brucellosis in dairy animals. To disseminate the information among dairy farmers regarding brucellosis prevention in dairy animals an â€œEducational moduleâ€ was developed and the action research study explored the feedback on the module. The findings revealed that majority of the respondents were highly satisfied with information function of educational module followed by subject qualityÂ and functionality component of educational module. Perceived feedback on effectiveness of different characteristics revealed that module meet the needs of target group, applicability of educational module in fieldÂ condition, color scheme used in information module, quantity of information provided and sufficient and simplicity of content for enhancing knowledge were ranked in respective order among the five component of information module.